2022
DOI: 10.1080/1478422x.2022.2105682
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature corrosion behaviour of plastically deformed AISI 304 stainless steel by friction stir welding in neutral and acidified chloride solutions

Abstract: Severe plastic deformation of 304L stainless steel plate was carried out by friction stirring under an isothermal tool temperature at 825°C. The friction stirred zone showed extensive grain refinement, high fraction of low angle grain boundaries due to dislocation rearrangement, Σ3 and Σ9 special grain boundaries and discrete Fe-Cr-Mn-rich particles. Electrochemical polarisation measurements were done on the base metal (BM) and friction stir welded (FSW) specimens in the neutral and acidified 3.5% NaCl solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
(61 reference statements)
0
0
0
Order By: Relevance
“…Friction stir welding or processing (FSW or FSP) is another surface modification process that leads to grain refinement, low-angle grain boundaries, and compressive residual stress distribution on the stirred zone (SZ) [26]. The friction-stirred 304L material showed better resistance to pitting corrosion in the acidified chloride solution than the base metal (BM) in mill-annealed conditions [27,28]. Therefore, FSW and FSP can be beneficial in preventing SCC damage in austenitic SS structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Friction stir welding or processing (FSW or FSP) is another surface modification process that leads to grain refinement, low-angle grain boundaries, and compressive residual stress distribution on the stirred zone (SZ) [26]. The friction-stirred 304L material showed better resistance to pitting corrosion in the acidified chloride solution than the base metal (BM) in mill-annealed conditions [27,28]. Therefore, FSW and FSP can be beneficial in preventing SCC damage in austenitic SS structures.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies showed that friction stir welding of 304L resulted in excessive grain refinement due to heavy plastic deformation and a higher fraction of low-angle grain boundaries due to dislocation rearrangement [27,28]. The low-angle grain boundaries could supply more misorientation dislocations at the metal/film interface, forming anion vacancies by a dislocation-climb process.…”
Section: Introductionmentioning
confidence: 99%